Pressure and Size of CR Balloon for adequate Papillary Dilatation during Therapeutic ERCP- an Experience from Pakistani Population - Warda Waheed, Sadia Tabassum, Sabeen Saleema Ahmed, Abeer Makhmoor, Sehrish Nadeem, Tayyab Saeed Akhter, Warda Waheed, Sadia Tabassum, Sabeen Saleema Ahmed, Abeer Makhmoor, Sehrish Nadeem, Tayyab Saeed Akhter (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Background: Choledocholithiasis is a rising problem and methods for removal of bile stone are under evolution with advent of new technologies like endoscopic techniques. This study explored the mean size of balloon, mean pressure of balloon and mean duration of procedure in patients undergoing therapeutic Endoscopic Retrograde cholangiopancreatography (ERCP) presenting to a tertiary care hospital in Pakistan. Methods: This cross-sectional descriptive study was conducted at the Liver center of Holy Family Hospital from May 2016 to August 2016. 36 patients with referral for ERCP because of bile duct lithiasis, age greater than 20 years, patients giving informed consent prior to ERCP, patients with CBD stone less than or equal to 12mm diagnosed by Computerized tomography or ultrasound were included in the study. Patients with previous surgery of biliary tract, pancreatobiliary malignancy, anticoagulation therapy within 72 hours of procedure and those with biliary colic fistula were excluded from the study. Results: Amongst 36 patients, 14(38.8%) were male and 22(61.11%) were female. The smallest recorded balloon size was 8.0 mm, largest 30 mm with mode of 15 and mean 17±4.28 mm. The minimal Mean balloon pressure was observed to be 20 psi, maximum being 66 with a mode of 50, median 47.50 and mean 44.85 ± 11.38 psi. The mean duration of successful stone removal was 47.07 ±24.29 minutes the shortest procedure was of 15 minutes while the longest was of 120 minutes with a mode of 30 minutes and median of 45 minutes. Conclusion: Successful therapeutic intended ERCP was observed even with minimal balloon dilatation and balloon pressure.